Sporadic Model as Applied Islamic Education: an Integration? - Ahmad Halid (TSAQAFAH, 2023)
This article examines the sporadic evaluation model of learning at Madrasah Tsanawiyah (MTs). Sporadic evaluation of learning has succesfully integrated in MTs. because it emphasizes the novelty aspect (the hallmark of the school). This sporadically has been carried out with its own model, the school certainly has considered the government system such as the Ministry of Education and Culture and the Ministry of Religion of the Republic of Indonesia. However, it is considered that there are many weaknesses so that the school uses its own school method, especially the COVID-19 pandemic atmosphere. This study uses qualitative and data collection methods using observation, interviews, and documentation with sharpened data analysis of the Milles and Huberman models. The validity of the data using source triangulation. This research problem is very interesting to study and the aim is that this sporadic model becomes a new breakthrough in increasing the effectiveness of active learning, learning innovativeness, initiative-creative, learning flexibility, self-development, quality learning (perfectionism)and achieving school goals well. Here i state, that sporadic model can be integrated in Islamic Educational system.